Transformation of Waste Banks: Realizing a Community- Based Circular Economy in Kwadungan Gunung Village,Kledung District,Temanggung Regency - Manurung, Herlina; Rokhaniyah, Siti; Khotijah, Siti Afidatul; Susilo, Ghina Fitri Ariesta; Khabibah, Nibras Anny; Febriyanti, Siti; Setyaningsih, Ratna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Waste management issues in Kwadungan Gunung Village, Kledung District, Temanggung Regency, present significant challenges to achieving environmental sustainability and community economic resilience. The increasing volume of household and agricultural waste, limited public awareness of circular economy principles, and suboptimal management of the existing waste bank constitute the core problems in this community. This study aims to optimize the role of the waste bank as a center for education, innovation, and community-based economic empowerment. The implemented methods include socialization and education on circular economy practices, training in waste utilization, and assistance for micro, small, and medium enterprises (MSMEs) in transforming waste into economically valuable products. The strategies involve developing a more structured operational system for the waste bank, providing community incentives, and fostering cross-sector collaboration with local stakeholders. The primary outputs of this program include publication of a scientific article in a nationally indexed (SINTA) journal, activity posters illustrating the workflow and program impact, implementation documentation, and copyright registration for the training module and waste bank management system. The outcomes are expected to position Kwadungan Gunung Village as a model of sustainable rural development, effectively implementing circular economy principles through the optimization of a community-based waste bank.